Selinexor, a First in Class, Nuclear Export Inhibitor for the Treatment of Advanced Malignant Peripheral Nerve Sheath Tumor. (17th February 2021) - Al‐Ezzi, Esmail; Gounder, Mrinal; Watson, Geoffrey; Mazzocca, Alessandro; D'Angelo, Sandra P.; Bravetti, Julie; Wang, Hongwei; Abdul Razak, Albiruni; Vincenzi, Bruno
Abstract: Malignant peripheral nerve sheath tumor (MPNST) is a highly malignant neoplasm arising from peripheral nerve or its attendant sheath and is derived from Schwann or pluripotent cells of neural crest origin. Patients with recurrent, unresectable, or advanced stage disease have limited treatment options, and current therapies are associated with little benefit. In this article, we report nine cases of MPNST treated with selinexor, an orally bioavailable, selective inhibitor of nuclear export, accompanied by tumor stabilization or regression. Abstract : This brief communication describes the experience of three large sarcoma oncology centers with a novel inhibitor of nuclear export in a rare sarcoma: malignant peripheral nerve sheath tumor. A possible treatment option is reported.